Utility-based approach for utilising services of mobile devices in mobile grid. (24th June 2011) - Chunlin, Li; Layuan, Li
This paper presents a utility-based approach for utilising services of mobile devices in mobile grid. This paper proposes a computational model for the calculation of utilities of the negotiating service agents and user agents in mobile grid system. The proposed model uses multiple attribute (energy consumption and resource utilisation) in the utility function. The goal is the maximisation of utility for the mobile grid system. To reduce the computational complexity, the global optimisation is decomposed into subproblems at two levels. Furthermore, the paper presents a utility-based algorithm for optimally exploiting mobile devices to support mobile services in mobile grid. Finally, the paper illustrates the effectiveness and performance through a set of simulations and evaluations.